Anáforas encapsuladoras na voz do narrador de menino de engenho - Andrade, Maria José Cavalcanti de (2015)
This Anaphoras dissertation entitled encapsulating the voice of the Menino de engenho narrator aims to first identify the anaphoric tunnels that occur in some fragments of the voice of the narrator of the novel by José Lins do Rego. About the anaphora, observe its importance in the context in which they are being used, facilitating the understanding of the meaning of the objects of-speech previously placed in the text. Taking into account the studies on the textual linguistics, specifically the theory of referencing, we rely on the theoretical framework of Koch's work (2011b, 2014); Koch & Elias (2012); Mondada & Dubois (2003); Cavalcante (2013); Cortez (2012) to support research on anaphora. In addition, we aim to discuss the encapsulation anaphora in the narrator's voice, which gave us the light of polyphony Oswald Ducrot (1987), distinguish the narrator / announcer of the narrator / enunciator. In addition, there is a "mess" of voices, given that arises the question: now is o narrador / announcer who comes or the narrator / enunciator? From this, we saw the relevance of voice identification context that sets out. Analyzed, from studies on the encapsulation anaphora and polyphonic theory Ducrot, some fragments of the work that prove the tunnels and their relationship to the voice of the narrator. Anaphoric expressions strengthen said by the narrator and reveal the statements by the voices that arise in the context. The choice of such literary canon is due to the analogy between narrative and memoir itself anaphora by the fact that in both there is a return movement, which is getting back something that was lived (in the case of the narrative) or what was said (in case of anaphora). The narrative memoir worked not in the bias of literariness itself, but the analysis of the multitude of voices that arise in anaphoric expressions highlights the relevance of linguistic studies and their uses in the literary work in question which, in turn, reflects the plurality of action and says something about the real world.